Pain Coping Profiles in Workers' Compensation Clients with Chronic Musculoskeletal Pain: A Cluster Analysis. Issue 2 (9th November 2015) - Sanchez, Jennifer; Brooks, Jessica; Fitzgerald, Sandra; Strand, David M.; Leczycki, Aneta; Blake, John; Chan, Fong; Lee, Gloria K.
Abstract : This study investigated pain coping profiles using the Coping Strategies Questionnaire-24 (CSQ-24) in a sample of 171 workers' compensation clients with chronic musculoskeletal pain from Canada. Cluster analysis identified three distinct coping profiles: mixed coping, catastrophising, and positive coping. Multivariate analysis of variance (MANOVA) results revealed that the positive coping group had lower levels of activity interference and depression as well as higher levels of quality of life than the mixed coping and catastrophising groups. Study findings indicate clients with chronic musculoskeletal pain can be categorised according to pain coping strategies, and pain coping strategies used are related to rehabilitation outcomes. The implications of these pain coping profiles for rehabilitation counselling practice are discussed.